2012
DOI: 10.1111/j.1462-5822.2012.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells are recruited during pulmonary tuberculosis and theirex vivoresponses to mycobacteria vary between healthy human donors in association withKIRhaplotype

Abstract: SummaryHumans vary widely in their susceptibility to tuberculosis. While only a minority will progress to disease, the majority of healthy individuals exposed to Mycobacterium tuberculosis mount an immune response that can clear or contain the infection in a quiescent form. Using immunofluorescence on human clinical samples, we identified natural killer (NK) cells infiltrating granulomatous pulmonary lesions during active disease. In order to compare the NK cell ability to react to free mycobacteria in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 43 publications
(54 reference statements)
3
61
0
Order By: Relevance
“…These results are consistent with previous observations that macaques not only lose bacillus Calmette-Guérin vaccination-induced protective immunity upon experimental depletion of CD8 + T cells, but also reactivate Mtb infections suppressed by chemotherapy at a higher rate (13). In addition, the presence of CD3 − cells producing granzyme lends credibility to the role of NK cells in mediating control of both SIV and Mtb infection (37,38). The effector role of CD8 + T cells in the control of Mtb infection in humans has recently been described to inversely correlate with bacterial load in sputum (39), and HIV coinfection can impair Mtb-specific CD8 + T degranulation and proliferation (40).…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with previous observations that macaques not only lose bacillus Calmette-Guérin vaccination-induced protective immunity upon experimental depletion of CD8 + T cells, but also reactivate Mtb infections suppressed by chemotherapy at a higher rate (13). In addition, the presence of CD3 − cells producing granzyme lends credibility to the role of NK cells in mediating control of both SIV and Mtb infection (37,38). The effector role of CD8 + T cells in the control of Mtb infection in humans has recently been described to inversely correlate with bacterial load in sputum (39), and HIV coinfection can impair Mtb-specific CD8 + T degranulation and proliferation (40).…”
Section: Discussionsupporting
confidence: 81%
“…obs.] and others [58], and it may explain, at least in part, the discrepancies observed in different studies. The recent discovery that NK cells may express immunological memory [38,39,40] suggests the attractive hypothesis that the variability in NK cell responses could be related to differences among donors in the degree of sensitization to mycobacterial antigens, due to previous exposure to BCG vaccination or environmental mycobacteria.…”
Section: Direct Mycobacterial Recognition and The Role Of Nk Cell Recmentioning
confidence: 95%
“…Another explanation for the inter-individual variability in the NK cell responses could be related to the expression of specific human leukocyte antigen/KIR haplotypes. It has recently been proposed that KIR B haplotypes are correlated to a higher responsiveness of NK cells to extracellular mycobacteria [58]. …”
Section: Direct Mycobacterial Recognition and The Role Of Nk Cell Recmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NK cells from patients with latent TB contribute to adaptive immunity against MTB by enhancing the mycobacteria-specific CD8 + T cell effector functions [4] and by inhibiting expansion of regulatory T cells [21]. Recently, it has been reported that NK cells are recruited within mature granulomatous lesions of TB patients suggesting that they may play a role not only in the early phases of TB infection, but also at later time points [22].…”
Section: Introductionmentioning
confidence: 99%